Valorization of solid waste using advanced thermo-chemical process: A review. Issue 4 (August 2021) - Bhatt, Mukesh; Chakinala, Anand Gupta; Joshi, Jyeshtharaj B.; Sharma, Anita; Pant, K.K.; Shah, Kalpit; Sharma, Abhishek
Abstract: Global economic development and continuous rise in the standard of living has led to resource depletion and increased per capita waste generation and, thus waste management issue becomes crucial. Sustainable development and circular economy require prominent technology for reducing the pace of resource depletion while producing alternatives to meet future energy demands. Municipal Solid Waste (MSW) is a potential source of interest for the recovery of either secondary raw material or to produce energy. At present, most of the MSW in waste treatment plants is converted into recyclable fractions called Refuse Derived Fuel (RDF) through the process of Mechanical Biological Treatment (MBT) with the aim of reducing environmental concerns and increasing its value. The focus of this review is to evaluate the importance of a thermo-chemical process for conversion of RDF into fuel and value-added products as well as evaluating applicability of this process in waste management sector and solid waste treatment. However, due to heterogeneous nature of RDF, investigation of co-pyrolysis behavior of RDF components as well as reaction mechanisms in both catalytic and non-catalytic reactions has been conducted. It has been observed that a high H/C, low O/C ratio and lower biomass content in RDF feed produces better quality products and decreases the dioxins emission during pyrolysis. Interactions of free radicals produced from polymer components with biomass greatly affect the product distribution. Chemicals derived out of RDF pyrolysis have been discussed and effect of various catalysts in enhancing oil yield and quality has been summarized. Catalytic pyrolysis with the use of P, Ni, Co, and Mo modified zeolite catalyst improves the quality of oil, and also the activity and catalyst lifetime. Different reactor technologies available for solid waste valorization have also been analyzed. Graphical Abstract: ga1 Highlights: Quality of RDF produced from MSW pre-treatment is investigated to ensure valorization process efficiency and product quality. Interaction behavior of different components and their mechanistic studies during thermal decomposition have been discussed. Reactor technologies for RDF processing are discussed in terms of their advantages and disadvantages.